Implementasi model pembelajaran aswaja untuk membentuk muslim berkarakter religius-nasionalis - M. Alifudin Ikhsan; Faris Khoirul Anam; Yusuf Hanafi; Abdul Adzim; Zahrotul Muzdalifah (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Through the implementation of the Aswaja learning model in schools, this community service aims to develop Muslims with religious-nationalist personalities.It was carried out in three phases of activities, namely education & outreach, implementation & strengthening and intensive mentoring from March to May 2021 at SMP Darul Faqih Indonesia, Malang Regency. The results of the activity assessment showed a change in Aswaja's attitudes and practices in fostering religious-nationalist values in students. This also has implications for strengthening religious moderation in the school environment. The results of the correlation test of students' attitudes and practices showed a score (R-square: P-value) of 0.126: 0.000, which indicates that this activity has a significant impact. The implementation of the Aswaja learning model is aimed at providing a balanced understanding of religion and nationalism. Strengthening the understanding of religious moderation with a nationalism - religious spirit will be an important ingredient in the development of peace culture education-based schools in Indonesia